(untitled) (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Trung NB, Dung TT, Thi QVC. 2024. Investigation of streptococcosis (Streptococcus iniae) as a cause of popeye and hemorrhagic disease in tilapia (Oreochromis niloticus) in the Mekong Delta, Vietnam. Biodiversitas 25: 3032-3040. Streptococcus iniae, is a dangerous pathogen that causes serious harm to several aquatic animals around the world. The current study aimed to isolate, characterize, and assess the pathogenicity of the Streptococcus iniae that causes popeye and hemorrhagic diseased nile tilapia (Oreochromis niloticus Linnaeus, 1758) in the Mekong Delta, Vietnam. Infected tilapia showed disorienting or lethargic swimming, exophthalmia (unilateral or bilateral), corneal opacity, and hemorrhages on the body, the operculum, and the abdomen of the fish. Upon internal examination, the diseased fish were found to have a pale liver, swollen kidney, and white or yellow fluid accumulation in the abdominal cavity. With the use of the API 20Strep Kit, conventional techniques, and 16S rRNA gene sequencing, a total of 16 isolates were determined to be S. iniae. They are Gram-positive bacteria, cocci or streptococci, with ?-hemolysis and small, white, opalescent colonies on BHIA medium after 24-36 hours of incubation at 28ºC. The obtained challenge tests showed that both isolates of RPBT02 and RPHG36 were highly virulent to fish, with LD50 values determined to be 2.34×104 and 1.81×104 CFU/mL, respectively. Interestingly, the two isolates of RPHG36 and RPBT02 in this study contained the virulence gene phosphoglucomutase (pgm), one of the factors that make S. iniae enhance antibiotic resistance and phagocytosis of the immune system by the host. These results of the study are important information for finding effective ways to control this bacterium in tilapia in the future.